NATIVE COPPER ORE-GENESES AT STAGES OF RIPHEAN-VENDIAN RIFTFORMING - DEREVSKA, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Development of native copper ore forming system was featured by intricate history. Conditions and character of ore forming process were differ at each stage of the Riphean-Vendian rift trough formation process. According to this fact the mineralization occurences morphology is individual for each stage of the ore forming system development. Observed mineralized zones are changed from autometasomatic and "parahydrothermal" impregnated native copper zones to hydrothermal copper sulphide impregnations and veinlets.